All-carbon phosphoranes via difluorocarbene trapping. Issue 39 (16th April 2021) - Smirnov, Vladimir O.; Volodin, Alexander D.; Korlyukov, Alexander A.; Dilman, Alexander D.
Abstract : A reaction of intramolecularly disposed phosphonium and phenoxide (or thiophenoxide) fragments with difluorocarbene affording all-carbon λ 5 -phosphoranes is described. Abstract : A reaction of intramolecularly disposed phosphonium and phenoxide (or thiophenoxide) fragments with difluorocarbene affording all-carbon λ 5 -phosphoranes is described. The presence of electron-withdrawing CHF2 -groups at the phosphonium center is important for the phosphorane formation. In a phosphorane, both phenyl groups located in the equatorial positions undergo 1, 2-P, C migration under thermal conditions.